Nanoporous Morphogenesis in Amorphous Carbon Layers: Experiments and Modeling on Energetic Ion Induced Self‐Organization. Issue 7 (2nd June 2021) - Hoffmann, Daniel T.; Dietrich, Johannes; Mändl, Stephan; Zink, Mareike; Mayr, Stefan G.
Abstract: Nanoporous amorphous carbon constitutes a highly relevant material for a multitude of applications ranging from energy to environmental and biomedical systems. In the present work, it is demonstrated experimentally how energetic ions can be utilized to tailor porosity of thin sputter deposited amorphous carbon films. The physical mechanisms underlying self‐organized nanoporous morphogenesis are unraveled by employing extensive molecular dynamics and phase field models across different length scales. It is demonstrated that pore formation is a defect induced phenomenon, in which vacancies cluster in a spinodal decomposition type of self‐organization process, while interstitials are absorbed by the amorphous matrix, leading to additional volume increase and radiation induced viscous flow. The proposed modeling framework is capable to reproduce and predict the experimental observations from first principles and thus opens the venue for computer assisted design of nanoporous frameworks. Abstract : Self‐organized morphogenesis of nanoporous sponge‐like structures is experimentally observed when exposing amorphous carbon surfaces to energetic ions at elevated temperatures. Using a multiscale approach by coupling molecular dynamics simulations to a phase field model allows to track down i) clustering of vacancy‐like defects and ii) viscous creep mediated by interstitial‐like entities as key underlying mechanisms.